LN

chứng minh rằng   :   \(m^3n-mn^3\) chia hết cho 6 với mọi m.n thuộc Z

NC
23 tháng 2 2019 lúc 14:23

Nhận xét: với mọi a thuộc Z

 \(a\left(a^2-1\right)=\left(a-1\right).a.\left(a+1\right)\)chia hết cho 3 và chia hết cho 2

mà (3, 2)=1

=> \(a\left(a^2-1\right)\)chia hết cho 6 (1)

Với mọi m, n thuộc Z

\(m^3n-mn^3=mn\left(m^2-n^2\right)=mn\left[\left(m^2-1\right)-\left(n^2-1\right)\right]=mn\left(m^2-1\right)-mn\left(n^2-1\right)\)

Từ (1) => \(m\left(m^2-1\right)⋮6,n\left(n^2-1\right)⋮6\)=> \(m^3n-mn^3⋮6\)với mọi m, n thuộc Z

Bình luận (0)